Histological evidence supporting the durability of successful radiofrequency renal denervation in a normotensive porcine model. Issue 10 (18th October 2022) - Sharp, Andrew S.P.; Tunev, Stefan; Schlaich, Markus; Lee, David P.; Finn, Aloke V.; Trudel, Julie; Hettrick, Douglas A.; Mahfoud, Felix; Kandzari, David E.
Abstract : Background: Sustained blood pressure reductions after radiofrequency (RF) renal denervation (RDN) have been reported to 3 years in patients with uncontrolled hypertension. However, mechanistic data to support procedural durability are lacking. We aimed to quantify the long-term nerve anatomic and functional effects of RF RDN in a preclinical model. Methods: Bilateral RF RDN was performed in 20 normotensive swine. Renal tissue samples were obtained in the RDN-treated groups at 7 ( n = 6), 28 ( n = 6), and 180 days ( n = 8) postprocedure for quantification of cortical norepinephrine (NE) levels and renal cortical axon density. Tissue fibrosis, necrosis and downstream nerve fiber atrophy (axonal loss) were also scored for each sample. Three additional untreated groups ( n = 6, n = 6 and n = 8, respectively) served as control. Results: Pathologic nerve changes were characterized by necrosis in the ablated region at 7 days that partially resolved by 28 days and fully resolved at 180 days. Axonal loss was apparent within and downstream to the ablation regions and was evident at 7, 28 and 180 days in the main vessel and branch vessels. Consequently, renal cortical axon density and corresponding cortical NE levels were significantly reduced at 7 days in the RDN vs. control group and remained suppressed at 180 days. Conclusions: Reductions in renal NE, cortical axon density and downstream axonal loss caused by axonal destruction persisted through 180 days post-RDN in a normotensive swine model. These results suggest functional nerve regrowth after RF RDN is unlikely and support published clinical evidence that the procedure results in durable blood pressure reduction.